Correlation between red cell distribution width and coronary artery disease in patients undergoing elective coronary angiography - Latif, Sayem Bin; Das, Prabir Kumar; Awal, Anisul; Dev, Saurav; Ismail, Khondaker M.; Bashiruddin, M. A. B. K.; Mohammad Omar Faroque, Abu Sayem; Bhattacharyya, Debabrata; Hossain, M. Sawkat; Bhattacharyya, Partha (International Journal of Research in Medical Sciences, 2023)
Background: Coronary artery disease (CAD) is the primary cause of death in developed countries and is one of the leading causes of disease burden in developing countries. Methods: This descriptive cross-sectional study included 124 purposively selected patients who underwent elective CAG in the department of cardiology, Chittagong medical college hospital, Chattogram, from July 2020 to June 2021. SPSS 23.0 software was used for processing and analysis at the end of the data collection period. Results: According to the Gensini score, patients were categorized into two groups (score <30 and ≥30). There were no significant differences between the two groups concerning BMI, smoking, hypertension, DM, F/H of CAD, statin or beta-blocker use, or the levels of hemoglobin, hematocrit, MCV, MCH MCHC, and creatinine. However, the mean age was older, and there were more males in the severe CAD group. The percentage of dyslipidemia was significantly higher in patients with Gensini score ≥30 than in patients with <30. RDW (OR: 2.629; 95% CI: 1.425-4.484; p=0.002) and age (OR: 1.058; 95%CI: 1.00-1.111; p=0.027) were independently correlated with the severity of CAD. The AUROC for red cell distribution width (RDW) was 0.915 with a p<0.001 for predicting CAD on CAG. It indicated a statistically significant association of RDW with the presence of CAD. A cut-off value of 13.65% RDW had a sensitivity of 80% and specificity of 84.2% for the prediction of CAD. There were no significant differences between patients with and without angiographic CAD for BMI, hypertension, DM, statin, or beta-blocker use, or of the levels of hemoglobin, hematocrit, MCV, MCH, MCHC, and creatinine. However, the mean age was older, and there were more males in the CAD group. The percentage with dyslipidemia, smoking, and F/H of CAD was significantly higher in patients with CAD than in patients without CAD. The data indicate that only RDW was independently correlated with the presence of CAD (OR: 2.593; 95% CI: 1.347-4.989; p=0.004). Conclusions: RDW is associated with the presence of CAD and suggests that it might be a readily available test for predicting coronary artery diseases.